Karakteristik Set Yogurt Instan Ekstrak Ubi Jalar Ungu dengan Variasi Penambahan Maltodekstrin - Sukarna, Riki; Fizriani, Atia; Tubagus, Robi (Program Studi Gizi, Universitas Bumigora, 2025)
Liquid yogurt has limitations in terms of distribution and shelf life; therefore, it has been developed in an instant form to improve product stability. The addition of purple sweet potato extract can enhance the functional value of instant set yogurt. The aim of this study was to determine the effect and identify the best treatment based on variations in maltodextrin concentration on the chemical and physical characteristics of instant set yogurt enriched with purple sweet potato extract. This study employed a Randomized Block Design (RBD) with one factor, consisting of four levels of maltodextrin addition (5%, 10%, 15%, and 20%) and three replications. The analyzed parameters included moisture content, ash content, total lactic acid, fat content, total solids non-fat, antioxidant activity, solubility, and yield. The results showed that maltodextrin had a significant effect on moisture content, ash content, solubility, yield, total lactic acid, antioxidant activity, and total solids non-fat, but did not significantly affect fat content. It was concluded that the best treatment was obtained with the addition of 20% maltodextrin, which produced the following characteristics: moisture content 10.20 ± 0.86%, ash content 2.94 ± 0.43%, total lactic acid 1.69 ± 0.06%, fat content 4.36 ± 0.09%, total solids non-fat 95.20 ± 0.05%, antioxidant activity 422.58 ± 13.30 ppm, solubility 85.71 ± 0.74%, and yield 34.06 ± 0.23%.